Решить. преобразуйте выражения, используя формулы сокращенного умножения. c²-16= (2x-1)= 16x²-25= x²+4x+4= (0,2-x)(0,2+x) = (0,5-x) = x²+9= (11-x) (x+11)= -8x+x²+16= x в 8 степени + y²= 25²+10x+1= -a²-2ab-b= 1-c³= -x²-2x-1=

kateshaginian kateshaginian    3   24.09.2019 18:30    2

Ответы
котик8308 котик8308  21.08.2020 14:58
(c-4)(c+4)
4x^2-4x+1
(4x-5)(4x+5)
(x+2)^2
0.04-x^2
0.25-x+x^2
(x+3)^2-3x
121-x^2
(x-4)^2
(x^4 + y) ^2-2x^4*y
(5x+1)^2 + 25^2 -25x^2
-(a+b)^2
(1-c) (1+c+c^2)
-(x+1)^2
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика